Defining Cost-Effective Solutions in Designing Marine Protected Areas, Using Systematic Conservation Planning - Galparsoro, Ibon; Borja, Ángel (Frontiers in Marine Science, 2021)
Currently, marine environmental conservation is one of the main objectives of management. It is agreed that effective management requires evaluating the tradeoffs between conservation and economic costs for negatively impacted maritime activities. For these reasons, integrated approaches combining ecological and socio-economic aspects are needed to achieve nature conservation and sustainability targets. Here, we present an approach for the identification of cost-effective priority areas for conservation through a Systematic Conservation Planning method, adopting the Basque country as case study (SE Bay of Biscay). Eight conservation scenarios were defined targeting a combination of conservation features: benthic habitats, biological value of cetaceans, birds, macroalgae and macroinvertebrates, ecosystem services provisioning potential and habitat sensitivity to human activities. In turn, the total fishing pressures produced by artisanal fisheries, was adopted as a measure of the socio-economic costs of the protection (assuming, for this research, that fishing would be banned in the protected areas). The results indicated that the existing marine protected areas (MPAs) were very close of achieving legally binding targets and that the targets could be achieved by increasing the size of the existing MPAs. The highest costs were associated to the declaration of areas that were targeting higher number of conservation features. Nevertheless, the cost/effectiveness was higher there, being the environmental benefits higher with a smaller increase of cost. In general, the most cost-effective scenarios were those that included the extension of declared MPAs. The framework implemented here permits an objective estimation of conservation targets achievement. This can assist managers and decision makers in identifying conservation gaps and ecosystem components on which they should pay attention. In addition, it can be used in the management strategies that should be adopted under different conservation scenarios. Thus, the approach proposed here could be used to inform the Ecosystem-based Marine Spatial Planning.